Comparative analysis of mouse and human preimplantation development following POU5F1 CRISPR/Cas9 targeting reveals interspecies differences. Issue 5 (20th February 2021) - Stamatiadis, P; Boel, A; Cosemans, G; Popovic, M; Bekaert, B; Guggilla, R; Tang, M; De Sutter, P; Van Nieuwerburgh, F; Menten, B; Stoop, D; Chuva de Sousa Lopes, S M; et al.
Abstract: STUDY QUESTION: What is the role of POU class 5 homeobox 1 ( POU5F1 ) in human preimplantation development and how does it compare with the mouse model? SUMMARY ANSWER: POU5F1 is required for successful development of mouse and human embryos to the blastocyst stage as knockout embryos exhibited a significantly lower blastocyst formation rate, accompanied by lack of inner cell mass (ICM) formation. WHAT IS KNOWN ALREADY: Clustered regularly interspaced short palindromic repeats—CRISPR associated genes (CRISPR-Cas9) has previously been used to examine the role of POU5F1 during human preimplantation development. The reported POU5F1 -targeted blastocysts always retained POU5F1 expression in at least one cell, because of incomplete CRISPR-Cas9 editing. The question remains of whether the inability to obtain fully edited POU5F1 -targeted blastocysts in human results from incomplete editing or the actual inability of these embryos to reach the blastocyst stage. STUDY DESIGN, SIZE, DURATION: The efficiency of CRISPR-Cas9 to induce targeted gene mutations was first optimized in the mouse model. Two CRISPR-Cas9 delivery methods were compared in the B6D2F1 strain: S-phase injection (zygote stage) (n = 135) versus metaphase II-phase (M-phase) injection (oocyte stage) (n = 23). Four control groups were included: non-injected media-control zygotes (n = 43)/oocytes (n = 48); sham-injected zygotes (n = 45)/oocytes (n = 47); Cas9-protein injected zygotes (n = 23); and Cas9 protein and scrambled guide RNA (gRNA)-injected zygotes (n = 27). Immunofluorescence analysis was performed in Pou5f1 -targeted zygotes (n = 37), media control zygotes (n = 19), and sham-injected zygotes (n = 15). To assess the capacity of Pou5f1-null embryos to develop further in vitro, additional groups of Pou5f1 -targeted zygotes (n = 29) and media control zygotes (n = 30) were cultured to postimplantation stages (8.5 dpf). Aiming to identify differences in developmental capacity of Pou5f1 -null embryos attributed to strain variation, zygotes from a second mouse strain—B6CBA (n = 52) were targeted. Overall, the optimized methodology was applied in human oocytes following IVM (metaphase II stage) (n = 101). The control group consisted of intracytoplasmically sperm injected (ICSI) IVM oocytes (n = 33). Immunofluorescence analysis was performed in human CRISPR-injected (n = 10) and media control (n = 9) human embryos. PARTICIPANTS/MATERIALS, SETTING, METHODS: A gRNA-Cas9 protein mixture targeting exon 2 of Pou5f1 / POU5F1 was microinjected in mouse oocytes/zygotes or human IVM oocytes. Reconstructed embryos were cultured for 4 days (mouse) or 6.5 days (human) in sequential culture media. An additional group of mouse-targeted zygotes was cultured to postimplantation stages. Embryonic development was assessed daily, with detailed scoring at late blastocyst stage. Genomic editing was assessed by immunofluorescence analysis and next-generation sequencing. MAIN RESULTS AND THE ROLE OF CHANCE: Genomic analysis in mouse revealed very high editing efficiencies with 95% of the S-Phase and 100% of the M-Phase embryos containing genetic modifications, of which 89.47% in the S-Phase and 84.21% in the M-Phase group were fully edited. The developmental capacity was significantly compromised as only 46.88% embryos in the S-Phase and 19.05% in the M-Phase group reached the blastocyst stage, compared to 86.36% in control M-Phase and 90.24% in control S-Phase groups, respectively. Immunofluorescence analysis confirmed the loss of Pou5f1 expression and downregulation of the primitive marker SRY-Box transcription factor ( Sox17) . Our experiments confirmed the requirement of Pou5f1 expression for blastocyst development in the second B6CBA strain. Altogether, our data obtained in mouse reveal that Pou5f1 expression is essential for development to the blastocyst stage. M-Phase injection in human IVM oocytes (n = 101) similarly resulted in 88.37% of the POU5F1-targeted embryos being successfully edited. The developmental capacity of generated embryos was compromised from the eight-cell stage onwards. Only 4.55% of the microinjected embryos reached the late blastocyst stage and the embryos exhibited complete absence of ICM and an irregular trophectoderm cell layer. Loss of POU5F1 expression resulted in absence of SOX17 expression, as in mouse. Interestingly, genetic mosaicism was eliminated in a subset of targeted human embryos (9 out of 38), three of which developed into blastocysts. LIMITATIONS, REASONS FOR CAUTION: One of the major hurdles of CRISPR-Cas9 germline genome editing is the occurrence of mosaicism, which may complicate phenotypic analysis and interpretation of developmental behavior of the injected embryos. Furthermore, in this study, spare IVM human oocytes were used, which may not recapitulate the developmental behavior of in vivo matured oocytes. WIDER IMPLICATIONS OF THE FINDINGS: Comparison of developmental competency following CRISPR-Cas-mediated gene targeting in mouse and human may be influenced by the selected mouse strain. Gene targeting by CRISPR-Cas9 is subject to variable targeting efficiencies. Therefore, striving to reduce mosaicism can provide novel molecular insights into mouse and human embryogenesis. STUDY FUNDING/COMPETING INTEREST(S): The research was funded by the Ghent University Hospital and Ghent University and supported by the FWO-Vlaanderen (Flemish fund for scientific research, Grant no. G051516N), and Hercules funding (FWO.HMZ.2016.00.02.01). The authors declare no competing interests. TRIAL REGISTRATION NUMBER: N/A.